An improvement in self-care behaviour in heart failure patients lead to better management of hypertension. (25th November 2020) - Sahlin, D.S; Gerward, S
Abstract: Background: A common heart failure (HF) aetiology is hypertension (HTN), second only to ischemic heart disease and with a prevalence in the HF community of between 62% and 84%, depending on sex and ejection-fraction. Undertreated HTN leads to worse prognosis and resistant HTN is defined as blood pressure (BP) exceeding 140/90 mmHg, in spite of pharmacological treatment. Since one constituent of self-care behaviour is treatment adherence, we wished to study whether patients exposed to a digital intervention shown to improve self-care behaviour, would also display improved BP control. Methods: SMART-HF was a randomized controlled trial, recruiting patients from seven centres in Region Skåne in southern Sweden, where patients in the intervention group (IG) were equipped with a digital home-based tool, designed to enhance self-care behaviour for HF-patients and the control group (CG) were subject to standard care. BP data was registered at baseline and after eight months of intervention and self-care behaviour was measured using the European Heart Failure Self-care Behaviour Scale (EHFScB). We used a Chi-square test to analyse whether there was an inter-group difference of prevalence of resistant HTN or a mean arterial pressure (MAP) outside the recommended range of 60 mmHg < MAP <100 mmHg. Results: Out of the 118 patients included in the original analysis, 92 (78%) had complete BP measurements. At baseline there was no difference in self-care behaviour between the groups, with CG: 25 [17.5; 32] and IG: 24.5 [18; 30], p=0.61, and 28% of the CG patients and 24% of the IG population displayed resistant HTN, p=0.73. After eight months of intervention the IG had 21% (or 4.5 points) better self-care behaviour compared to the CG, p=0.014, and the fraction of patients with resistant HTN was 30% for the CG and 11% for the IG, p=0.027. There was also a significant effect on the fraction of patients having a MAP >100 mmHg, with 22% in the CG versus 16% in the IG having MAP >100 mmHg at baseline (p=0.39) and 19% in the CG versus 0% in the IG at follow-up (p=0.002). Conclusions: There was a significant improvement in self-care behaviour and also a significant reduction in the number of patients with resistant hypertension and elevated mean arterial pressure after eight months of intervention. Funding Acknowledgement: Type of funding source: None